Does GLP-1 suppress its own basal secretion?. (2nd January 2016) - Elahi, Dariush; Ruff, Dennis A.; Carlson, Olga D.; Meneilly, Graydon S.; Habener, Joel F.; Egan, Josephine M.
Abstract: Purpose/Aim : Negative feedback controls in endocrine regulatory systems are well recognized. The incretins and their role in glucose regulation have been of major interest recently. Whether the same negative control system applies to the regulation of incretin secretion is not clear. We sought to examine the hypothesis that exogenous administration of glucagon like peptide-1, GLP-1(7–36) amide or its metabolite GLP-1(9–36) amide, reduces the endogenous basal release of this incretin. Materials and Methods : We evaluated the endogenous basal release of GLP-1 using two separate study designs. In protocol A we examined the GLP-1(7–36) amide levels during the infusion of GLP-1(9–36) amide. In protocol B, we used PYY and GLP-2 as biomarkers for the endogenous basal release of GLP-1(7–36) amide and assessed the endogenous basal release of these two hormones during the GLP-1(7–36) infusion. Twelve lean and 12 obese subjects were enrolled in protocol A and 10 obese volunteers in protocol B. Results : The plasma levels of GLP-1(7–36) amide in protocol A and PYY and GLP-2 in protocol B remained unchanged during the exogenous infusion of GLP-1(9–36) and GLP-1(7–36) amide, respectively. Conclusions : The negative feedback control system as described by inhibition of the release of endogenous hormone while infusing it exogenously was not observed for the basal secretion of GLP-1(7–36) amide.